2006
DOI: 10.1002/dir.20058
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of time-varying online price and price dispersion between multichannel and dotcom DVD retailers

Abstract: We compare price differences and market dynamics between two types of online retailers: online branches of multichannel retailers (OBMCRs) and pure Internet retailers (Dotcoms), based on a set of panel data collected from the DVD market. We find that (i) OBMCRs charge higher prices than Dotcoms, (ii) prices go up with time for both OBMCRs and Dotcoms, and (iii) prices of Dotcoms go up faster than those of OBMCRs.We also find that price dispersions of OBMCRs and Dotcoms are significantly different and the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 45 publications
(87 reference statements)
0
38
0
Order By: Relevance
“…The obtained results are inconsistent. For example, Pan (2003) finds that multichannel retailers have a lower level of price dispersion than do pure online retailers; while Xing et al, (2006), and Tang & Xing (2001) find a reverse result. The different results may be due to different measurement of price dispersion, product categories, and market differences, etc.…”
Section: Price Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results are inconsistent. For example, Pan (2003) finds that multichannel retailers have a lower level of price dispersion than do pure online retailers; while Xing et al, (2006), and Tang & Xing (2001) find a reverse result. The different results may be due to different measurement of price dispersion, product categories, and market differences, etc.…”
Section: Price Dispersionmentioning
confidence: 99%
“…But many studies repudiate this theory and find that although Internet market evolves as time progresses, price dispersion remains persistent (Pan et al, 2002;Pan, et al, 2004;Ratchford et al, 2003;Xing, et al, 2006).…”
Section: Price Dispersionmentioning
confidence: 99%
“…Although Bakos' theory is supported by Smith (2001), and Smith and Brynjolfsson (2001), Harrington (2001) disputed Bakos's results by demonstrating the absence of symmetric pure-strategy equilibrium in which consumers search. Since then, mounting empirical evidence points to the existence of persistent pricing differences in online markets (Pan et al, 2004;Xing et al, 2004;Xing et al, 2006). Theoretically, Baye and Morgan (2001) and Chen and Hitt (2003) both showed that online price dispersion can be an equilibrium outcome of price competition in the Internet markets.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…The rapid development of online retailing has inspired a fast growing research interest in studying the online pricing behaviors (Ancarani and Shankar, 2004;Pan et al, 2004;Xing, et al, 2006). Early studies in the literature mainly focused on comparing price levels and price dispersions between offline and online competitors (Bailey, 1998;Brynjolfsson and Smith, 2000), and among online retailers (Tang and Xing, 2001;Clemons et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation